2007
DOI: 10.2164/jandrol.106.001081
|View full text |Cite
|
Sign up to set email alerts
|

First Steps in the Development of a Functional Assay for Human Sperm Using Pig Oocytes

Abstract: The use of mammalian oocytes to assess human sperm functionality could be a helpful tool with potential applications in clinical and research programs. In an attempt to develop the pig model, the aim of the present work was to study the interaction between human spermatozoa and pig oocytes at the zona pellucida (ZP), the oolemma, and the ooplasm levels. In vitro matured pig oocytes and human spermatozoa from fertile and low-fertility donors were employed. The induction of the acrosome reaction by the ZP, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…So, ICSI is presented as one alternative way for in vitro production of monospermic zygotes. Moreover, recent findings show that heterologous ICSI could represent a powerful tool to study human sperm functionality using the pig as oocyte donor (Canovas et al. 2007).…”
Section: Origins and Applications Of Icsimentioning
confidence: 99%
“…So, ICSI is presented as one alternative way for in vitro production of monospermic zygotes. Moreover, recent findings show that heterologous ICSI could represent a powerful tool to study human sperm functionality using the pig as oocyte donor (Canovas et al. 2007).…”
Section: Origins and Applications Of Icsimentioning
confidence: 99%
“…These authors suggested that this difference correlates with the difference in the structure and composition of mouse and human or rat ZP. In addition, human spermatozoa have the capacity to bind to porcine ZP [47] but not to mouse ZP [17]. Many equine spermatozoa are able to bind to bovine ZP [48], but few bound to porcine ZP in our experiment.…”
Section: Discussionmentioning
confidence: 53%
“…Previous studies showed that bovine cytoplasm was able to decondense equine and human sperm chromatin after ICSI [66,67] and that porcine cytoplasm was able to decondense ovine, mouse, and human sperm chromatin after ICSI [47,68]. These data suggest that the molecules involved in sperm decondensation are at least partially conserved between mammalian species.…”
Section: Discussionmentioning
confidence: 62%
“…Sperm to zona attachment experiments were conducted as described previously [29] with some modifications. The number of attached spermatozoa was evaluated in oocytes from the homologous and heterologous IVF groups at 2.5 h of co-incubation 155 time.…”
Section: Assessment Of Attachment and Ivf Parametersmentioning
confidence: 99%